Prediction of fetal macrosomia using two-dimensional and three-dimensional ultrasound. (December 2019) - Mazzone, Eleonora; Dall'Asta, Andrea; Kiener, Ariane Jeanne Odette; Carpano, Maria Giovanna; Suprani, Alice; Ghi, Tullio; Frusca, Tiziana
Abstract: Objective: The estimation of the fetal weight by three-dimensional (3D) ultrasound (US) with fractional thigh volume (TVol) has been suggested to be more accurate than two-dimensional (2D) US particularly within the context of fetuses at risk of macrosomia. The objective of this study was to compare the accuracy of 2D US and 3D US with two different methods of projection for the identification of fetal macrosomia at term. Study design: Prospective study which included women at risk for fetal macrosomia referred for fetal biometry between 34 +0 -36 +6 weeks. The estimated fetal weight (EFW) was computed using 2D US and the Hadlock Model IV or through 3D US and the Model VI by Lee et al. The projection of the EFW at the time of delivery was performed by using Yudkin's chart percentiles and the gestation-adjusted projection (GAP) method. Results: Overall, 230 patients were included. Paired comparison between 2D-US-EFW and 3D-US-EFW with either method of projection of the EFW at birth suggested different properties of the techniques, being 2D-US-EFW associated with higher sensitivity and 3D-US-EFW with higher specificity, PPV and LR + . At ROC curve no difference was found in the prediction of birthweight ≥90th centile using 2D-US-EFW or 3D-US-EFW (AUC 0.831, 95%CI 0.768-0.894 versus AUC 0.860, 95%CI 0.799-0.920, respectively, p 0.37) nor in the prediction of birthweight >95th centile with 2D-US-EFW compared to 3D-US-EFW (0.803, 95%CI 0.731-0.874 versus 0.866, 95%CI 0.805-0.926, respectively, p 0.07). Similarly, a non-significant difference in the accuracy of the prediction of birthweight >4000 g (AUC 0.788, 95%CI 0.716-0.859 for 2D-US-EFW vs AUC 0.802, 95%CI 0.723-0.880 for 3D-US-EFW, p 0.72) and >4500 g (0.828, 95%CI 0.720-0.936 for 2D-US-EFW vs 0.858, 95%CI 0.759-0.956 for 3D-US-EFW, p 0.71) with the GAP method could be demonstrated. Conclusions: Within a population at risk of fetal macrosomia the performance of 3D-US-EFW is similar to that of 2D-US-EFW in the prediction of macrosomia at term regardless of the method used for the projection of the EFW, however different properties were noted between the two techniques. Such finding suggests a potential complementary role of the techniques which warrants evaluation in future research.